Copper-catalyzed borylative cyclization of γ, δ-unsaturated aromatic oxime esters to (borylmethyl)pyrrolidines. Issue 21 (25th September 2020) - Zhang, Youcan; Wu, Xiao-Feng
Abstract : An efficient copper-catalyzed aminoborylation of γ, δ-unsaturated aromatic oxime esters with bis(pinacolato)diboron has been developed. A variety of α-(borylmethyl)pyrrolidine derivatives were constructed in high yields under mild conditions. Abstract : An efficient copper-catalyzed aminoborylation of γ, δ-unsaturated aromatic oxime esters with bis(pinacolato)diboron has been developed. A variety of α-(borylmethyl)pyrrolidine derivatives were constructed in high yields under mild conditions. Notably, examples of converting the obtained aminoborylated product, including cycloaddition, oxidation, and coupling reactions, have been given as well.